2010
DOI: 10.1007/s00468-010-0437-6
|View full text |Cite
|
Sign up to set email alerts
|

Storage proteins and cell wall mobilisation in seeds of Sesbania virgata (Cav.) Pers. (Leguminosae)

Abstract: The endosperm of seeds of Sesbania virgata (Cav.) Pers. accumulates galactomannan as a cell wall storage polysaccharide. It is hydrolysed by three enzymes, one of them being a-galactosidase. A great amount of protein bodies is found in the cytoplasm of endospermic cells, which are thought to play the major role as a nitrogen reserve in this seed. The present work aimed at understanding how the production of enzymes that degrade storage compounds is controlled. We performed experiments with addition of inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…are known to induce carbohydrate mobilization in legume seeds (Brandão et al, 2009), and CKs likewise increase proteolytic activities and carbohydrate and lipid mobilization (Bewley et al, 2013). There is also evidence that ethylene induces galactomannan mobilization (Tonini et al, 2010) and the accumulation of ROS (which signal in the programmed cell death pathway) (Bailly, 2004;Gadjev et al, 2008;Gomes et al, 2014;Wojtyla et al, 2016). We observed that these processes resulted in the mobilization of cell wall carbohydrates, extravasation of cellular contents, and the extension of the range of collapsed cells in the adjacent endosperm of germinated B. capitata seeds.…”
Section: Discussionsupporting
confidence: 55%
“…are known to induce carbohydrate mobilization in legume seeds (Brandão et al, 2009), and CKs likewise increase proteolytic activities and carbohydrate and lipid mobilization (Bewley et al, 2013). There is also evidence that ethylene induces galactomannan mobilization (Tonini et al, 2010) and the accumulation of ROS (which signal in the programmed cell death pathway) (Bailly, 2004;Gadjev et al, 2008;Gomes et al, 2014;Wojtyla et al, 2016). We observed that these processes resulted in the mobilization of cell wall carbohydrates, extravasation of cellular contents, and the extension of the range of collapsed cells in the adjacent endosperm of germinated B. capitata seeds.…”
Section: Discussionsupporting
confidence: 55%
“…However, when seeds of S. virgata were incubated with a-amanitin, actinomycin-D, and cyclohehimide, different results were obtained (Tonini et al, 2010a), suggesting that the enzymes necessary for galactomannan degradation are already present, possibly in protein bodies. As storage protein degra-dation occurs, the hydrolases are released to the storage cell wall.…”
mentioning
confidence: 92%
“…The inhibitory effect of ABA during the degradation of proteins, mainly at the beginning of storage mobilization, can be related to the de novo synthesis of proteases and/or activation of the pre-formed proteases, as observed in seeds of barley (Hordeum vulgare) (Cercos et al, 1999), apple (Malus domestica) (Ranjan and Lewak, 1995), rice (Shintani et al, 1997) and bean (Phaseolus vulgaris) (Domash et al, 2006). Thus, it is likely that protein and carbohydrate metabolism might be linked to each other through their own catalytic processes so that the production and delivery of compounds related to carbon and nitrogen metabolism would be balanced during seedling development (Tonini et al, 2010).…”
Section: Aba May Connect Protein and Carbohydrate Metabolismsmentioning
confidence: 99%